Strategy Diversification Towards Firms Sustainability - wildan, khairul; Qayyum, Abdul (INTERNATIONAL JOURNAL OF ECONOMICS AND MANAGEMENT REVIEW, 2024)
Abstrak Purpose – This study aims to determine the diversification strategy has a significant positive effect on the sustainability of hospitality firms. Design/methodology/approach – The research method used is a literature study research method (Library Research) using an inductive analysis model originating from a number of literature which includes references to books that can support writing content and a number of internet sites that can add scientific vehicles as a support topic of discussion. Findings and Discussion – The results obtained in the study indicate that the diversification strategy has a significant positive effect on the sustainability of hospitality firms. Also, it has a significant positive moderating effect on the relationship between the diversification strategies sustainability of hospitality firms. Conclusion – A review of several previous journal studies yielded very positive results related to the diversification strategy for the sustainability of hospitality firms based on the research results concluding that hospitality firms must diversify their services or products to gain market share with customer support or improve organizational performance in the long term while at the same time sustainability.